Silicon’s Role in Modulating C:N:P Stoichiometry and Nutrient Release During Straw Decomposition in Maize and Sugarcane - Costa, Milton Garcia [UNESP]; de Oliveira, Tainara Lopes [UNESP]; de Mello Prado, Renato [UNESP]; da Silva, José Lucas Farias [UNESP]; de Farias Guedes, Victor Hugo [UNESP]; de Sousa Júnior, Jonas Pereira (Springer Nature, 2025)
This study aims to evaluate whether increased Si content in maize and sugarcane plants affects straw decomposition, stoichiometric ratios involving carbon (C), and nutrient release from straw. Two greenhouse experiments were conducted using straw from sugarcane and maize previously grown with and without Si supplementation. The treatments for both species included straw from cultivation without (0 kg ha⁻1) and with Si (10 kg ha⁻1), combined with five straw evaluation periods (0, 30, 60, 120, and 240 days of decomposition). The straw was packed in bags corresponding to 2 t ha⁻1. Si supplementation reduced the C:P and C:Si stoichiometric ratios in both species throughout the decomposition process, as well as the C:N ratio, with variations observed between the species. Si-enriched straw promoted faster decomposition and increased the rate of nutrient release, with maize straw showing a more pronounced effect compared to sugarcane straw. Si enhanced nutrient release at different rates depending on the species: for sugarcane, the release rates of K, Mn, Fe, N, and C increased, while for maize, the release rates of Cu, P, Ca, Fe, N, and C were enhanced. These findings suggest that Si can differentially influence nutrient cycling, potentially impacting the subsequent crop. These findings suggest that Si can differentially influence nutrient cycling, potentially impacting the subsequent crop.
Keywords: Agroecosystem; Beneficial element; Nutrient cycling; Saccharum officinarumL; Speed of decomposition; Zea maysL